The answer should be (A).

By simplifying the equation we get 2k + 3m = t

Does this mean that 2 and/or 3 are factors of t? Not necessarily!

Consider k=1 and m=1 => t=5. Does t have 2 and 3 as factors? No!

Alternately, consider k=3 and m=2 => t=12. In this case, t does have both k and m as factors.

Point to note:If a positive integer is the sum of the multiples of other positive integers, it need not be a multiple of either of the integers!

Carrying on with this question,

Using statement 1: If k is a multiple of 3, then the equation can be written as

2k + 3m = t

=> 2*3n + 3m = t (where n is a positive integer)

=> 3 (2n +m) = t

=> 3 is a factor of t

=> t and 12 have a common factor greater than 1 (i.e. 3)

SUFFICIENT.

Consider statement 2: If m is a multiple of 3, we can write the equation as

2k + 3m = t

=> 2k + 3*3n = t (where n is a positive integer)

=> 2k + 9n = t

If we take n=1 and k=3, we get t=15, which has 3 as a common factor greater than 1 with 12

If we take k=1 and n=1, we get t=11, which has no common factor greater than 1 with 12

Therefore statement 2 alone is insufficient.

The answer is (A).

_________________

GyanOne | Top MBA Rankings and MBA Admissions Blog

Top MBA Admissions Consulting | Top MiM Admissions Consulting

Premium MBA Essay Review|Best MBA Interview Preparation|Exclusive GMAT coaching

Get a FREE Detailed MBA Profile Evaluation | Call us now +91 98998 31738